The curricular structure of initial training in Physical Education in the state of Paraná: an analysis from public and private institutions (Research, Society and Development, 2020)
Objective: This work aimed to analyze how public and private institutions organize the curricula of the Bachelor of Physical Education course in the state of Paraná in the face of the dimensions of knowledge and the dynamics of workload. Methods: For this study were selected 14 institutions (7 public and 7 private) in six regions of the Paraná State/Brazil. After the selection of establishments, the curricular grids of the courses were analyzed, accounting and classifying the disciplines by dimensions of knowledge. For statistical analysis, Mann-Whitney, Qui-scare and Kruskal-Wallis non-parametric tests were performed. The results were described in frequencies, means, medians and interquartile range. Results: The dimension of knowledge with the highest percentage of disciplines is the “Technical-Instrumental”, which, in turn, suggests that the institutions are concerned with the technical training of Bachelor. In addition, private institutions have greater variability of disciplines, while public institutions have greater workload. The analysis also revealed differences between the regions when comparing the workload of the courses. Conclusions: There are distinctions in the way the curricula are organized, essentially in the composition of the dimensions of knowledge as well as in relation to the workload of these axes, which evidences, in a way, the autonomy and identity of the institutions in spite of the regulations and norms in force for structuring the courses.